PENGEMBANGAN E-MODUL BERBASIS CASE METHOD DAN PROJECT BASE MATA KULIAH KETERAMPILAN BERBAHASA INDONESIA DAN APRESIASI SASTRA SEKOLAH DASAR - Masta Marselina Sembiring; Erlinda Simanungkalit; Dody F. P. Ambarita; Dila Handayani (Universitas Negeri Medan, 2022)
The purpose of this research is to create a substantial Case Strategy and Venture Base E-Module item for Indonesian Dialect Abilities and Writing Appreciation Courses for Rudimentary Schools. This investigate employments investigate and advancement strategies or frequently called Investigate and Improvement (R&D). The area of the investigate was carried out at the Rudimentary School Educator Instruction Ponder Program, Workforce of Instruction, Medan State College. The population of this study were all students of the Stambuk 2021 Elementary School teacher program, a total of 225 students. The advancement of Case Method-Based E-Modules and Extend Base Dialect Abilities and Writing Appreciation Basic Schools has been approved by media specialists and gotten a possibility rate of 92%, whereas fabric specialists within the to begin with organize the feasibility percentage was 68.6% and after that expanded within the moment arrange, which was 85 %. The item was tried within the field on the normal lesson J 2021 understudies, totaling 22 individuals with a achievability rate rate of 96.2%. Based on the clarification over, it can be concluded that the Advancement of Case Method-Based E-Modules and Extend Base Dialect Abilities Addresses and Appreciation of Basic School Writing is suitable to be utilized to make strides learning results for Rudimentary School Instructor Instruction, Workforce of Instruction, State College of Medan.